The relationship between palm oil and soybean / Noor Fatihah Rizal and Nur Amalina Ismail - Rizal, Noor Fatihah; Ismail, Nur Amalina (Faculty of Plantation and Agrotechnology, 2018)
Palm oil is the largest produced and traded oil in the world. However, the major challenges such as soybean oil are that most of the oils are inter-substitutable and therefore in competition with each other. Palm oil and soybean are two agricultures commodities that have similar characteristics and are substitutable in many applications. Whenever there is increase in soybean oil price, the price of palm oil will follow suit. There are more than 17 major oils and fats produced and traded in the world. This paper investigates the price transmission in the world market for palm oil and soybean. The objective of this study is to determine the relationship between palm oil price and soybean price thus to determine the marketing strategy to make palm oil become dominant. By using the secondary annual data from year (1986-2016) for the variables, the relationship model been examined using two types of method. First method is Ordinary Least Square (OLS) or Multiple Regression. This method is used to see the relationship and significance of each variable. For this methods the results indicate that each variable are significant. The second method used is Impulse Response. It show the shock of one variable to another variable.